(untitled) (Innovation & Development in Engineering and Applied Science, 2023)
The risk of developing an occupational pathology due to exposure to noise can cause occupational clinical symptoms with short, medium or long term health effects. The objective of the study is to identify the dysergonomic magnitude of oscillating acoustic comfort, approximately between 80 and 85 decibels, in MSMEs of the metal-mechanic sector and its effects on workers’ exposure. The study population consisted of 1300 workers with a sample of 769 workers. The measurement was performed in different workstations with a sound level meter type 1, ISO 28803:2012 standard. Qualitative and quantitative data were obtained to analyze results related to occupational exposure. The sound pressure level was determined in each area of the plant during the different working days. This was done per worker according to their activity and tasks performed. In this way, it was possible to raise discussions about the improvement of the quality of life. The results of the study are satisfactory. Epidemiological surveillance programs (PVE) with an emphasis on audiometry are suggested.